INTERDEPENDENCY GROUP MODERATION AND THE RELATIONSHIP BETWEEN PROCEDURAL FAIRNESS AND AUDIT PERFORMANCE - Ardianto Ardianto (Journal of Economics, Business, and Accountancy Ventura, 2013)
This study is an experiment analyzing the subjects of the audit assignment group. This studyfocus on the dynamics in the aspects of behavior, especially the behavior which is related tothe relationship between the procedural fairness felt by the assignment group and the auditperformance. The method used is the basis of goal setting theory and valence instrumentalityexpectancy theory. Besides that, this study also tests the effect of the interdependence moderationon the relationship between group fairness and audit performance. By using defensetest with ANOVA, it provides result that interdependency moderation in the relationship betweenfairness and audit performance is high. This shows that procedural fairness felt by theteam influences the audit performance. The degree of the fairness effect on the audit performanceis also proved to be significantly influenced by the degree or level of interdependencyamong the groups.